Optimalisasi Pelaksanaan Supervisi di Ruang Bedah Rumah Sakit Umum Daerah Pringsewu - Puji Oktaviane Prasasti; Rizki Yeni Wulandari; Yunina Elasari (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Supervision should be scheduled and programmed, and if conducted continuously, it can ensure that nursing care is delivered in accordance with nursing practice standards. According to data in Indonesia, the average supervision by ward heads is categorized as less than satisfactory at 49.3%, while only 50.7% is considered good. This indicates that ward heads in various hospital departments are perceived as less effective by nurses in implementing their leadership, particularly regarding supervision. A pre-survey revealed the absence of a scheduled supervision timetable, guidelines/SOPs for supervision, and documentation of supervision results. This study aims to evaluate the implementation of supervision at the surgical ward of Pringsewu Regional Public Hospital. Data collection methods, conducted on November 9, 2024, included interviews, questionnaires, and observations. The findings identified a nursing management issue: the suboptimal implementation of supervision at the surgical ward of Pringsewu Regional Public Hospital. The planned activities included socialization on the application of supervision, supervision flow, and optimal supervision techniques. The implementation of these activities took place on December 20, 2024, through the socialization of supervision practices. The evaluation results after the socialization in the surgical ward showed that supervision was being carried out effectively. The ward head, team leader, and five nurses recognized the critical importance of supervision in improving the quality of care in the surgical ward. It is expected that the ward head (supervisor) will conduct supervision according to the established schedule, guidelines, and job descriptions, thereby enhancing the quality of nursing care in the surgical ward to achieve optimal outcomes.